2016
DOI: 10.48550/arxiv.1610.03113
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Truncated Variational Expectation Maximization

Abstract: We derive a novel variational expectation maximization approach based on truncated variational distributions. Truncated distributions are proportional to exact posteriors within a subset of a discrete state space and equal zero otherwise. The novel variational approach is realized by first generalizing the standard variational EM framework to include variational distributions with exact ('hard') zeros. A fully variational treatment of truncated distributions then allows for deriving novel and mathematically gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 34 publications
(112 reference statements)
2
31
0
Order By: Relevance
“…which approximate the full posterior by truncating sums over the whole latent space to sums over subsets K n) which accumulate most of the posterior mass [51,38]. The subsets K (n) can then be update, e.g., using evolutionary algorithms with fitness defined to be a monotonic function of the model joint p( s, y | Θ).…”
Section: Appendix a Additional Details On Parameter Update Equationsmentioning
confidence: 99%
“…which approximate the full posterior by truncating sums over the whole latent space to sums over subsets K n) which accumulate most of the posterior mass [51,38]. The subsets K (n) can then be update, e.g., using evolutionary algorithms with fitness defined to be a monotonic function of the model joint p( s, y | Θ).…”
Section: Appendix a Additional Details On Parameter Update Equationsmentioning
confidence: 99%
“…Centrally for this work, truncated posteriors allow a specific alternative reformulation of the bound that enables efficient optimization. The reformulation recombines the entropy term of the original form (2) with the first expectation value into a single term, and is given by (see Lücke, 2019, for details):…”
Section: Truncated Variational Optimizationmentioning
confidence: 99%
“…For our choice of variational distributions, it is not trivial that the entropy term actually can be ignored because the encoding model q Φ ( z; x) in (3) is defined in terms of the decoding model and its parameters. For truncated distributions, however, it can be shown that the entropy term can still be ignored(Lücke, 2019).…”
mentioning
confidence: 99%
“…Sheikh et al, 2014Sheikh et al, , 2019, we here apply a fully variational approach, i.e., we define a variational loop to optimize the variational parameters. Based on the specific functional form of truncated posteriors, optimal variational parameters Λ = (K, Θ) are given by setting Θ = Θ and by seeking K which optimize (see Lücke, 2019, for details):…”
Section: Evolutionary Optimization Of Truncated Posteriorsmentioning
confidence: 99%